2022
DOI: 10.3390/dj10090167
|View full text |Cite
|
Sign up to set email alerts
|

Viability and Adhesion of Periodontal Ligament Fibroblasts on a Hydroxyapatite Scaffold Combined with Collagen, Polylactic Acid–Polyglycolic Acid Copolymer and Platelet-Rich Fibrin: A Preclinical Pilot Study

Abstract: Background: Conventional periodontal therapy relies on bone regeneration strategies utilizing scaffolds made of diverse materials, among which collagen, to promote cell adhesion and growth. Objective: To evaluate periodontal ligament fibroblast (HPdLF) cell adhesion and viability for periodontal regeneration purposes on hydroxyapatite scaffolds containing collagen (HAp-egg shell) combined with polylactic acid–polyglycolic acid copolymer (PLGA) and Platelet-Rich Fibrin (PRF). Methods: Four variations of the HAp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, the improper use of traditional corticosteroid anti-inflammatory drugs, such as fluorometholone eye drops, tobramycin dexamethasone eye drops, and other drugs, can easily lead to diseases such as high intraocular pressure and cataract, thereby limiting their clinical use. In the field of ophthalmology, related research have shown that Tet can effectively inhibit the release of VEGF, IL-1β, PGE 2 , and TNF-α to achieve the goal of treating inflammatory diseases such as uveitis and conjunctivitis [ 27 , 28 ]. Therefore, this study hypothesized that Tet can effectively inhibit the expression of related inflammatory factors in DED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the improper use of traditional corticosteroid anti-inflammatory drugs, such as fluorometholone eye drops, tobramycin dexamethasone eye drops, and other drugs, can easily lead to diseases such as high intraocular pressure and cataract, thereby limiting their clinical use. In the field of ophthalmology, related research have shown that Tet can effectively inhibit the release of VEGF, IL-1β, PGE 2 , and TNF-α to achieve the goal of treating inflammatory diseases such as uveitis and conjunctivitis [ 27 , 28 ]. Therefore, this study hypothesized that Tet can effectively inhibit the expression of related inflammatory factors in DED.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the application of nanocarriers represents a promising means to selectively deliver and concentrate drugs in ocular. Besides, well-designed nanocarriers could contribute to enhancing the ability of corneal targeting for increasing drug concentration in the cornea surface, thus improving the therapeutic efficiency of loaded drugs [21, 22]. Polylactic/polyglycolic acid (PLGA) is a biodegradable functional polymer organic compound that is randomly polymerized from two monomers – lactic acid and glycolic acid.…”
Section: Introductionmentioning
confidence: 99%
“…(105) In the construction of dental and periodontal pulp for the preservation of periodontal ligament fibroblasts (PDLF), the use of PLGA scaffold combined with PRF has shown the ability to sustain fibroblast viability. (74,127) Various signaling molecules, including growth factors and cytokines have been recognized to enhance the proliferation, migration and differentiation of dental stem cells. These molecules are naturally contained in the pulpal cells and dentin matrix, and involved in modulating dentin-pulp complex homeostasis.…”
Section: Synthetic Biomaterials Scaffoldsmentioning
confidence: 99%
“…In particular, fewer cells proliferated in the PLGA-PEG composite film on day 7. It was concluded that HAP in the polymeric composite film was effective in the attachment and proliferation of chondrocytes (11,(48)(49)(50)(51).…”
Section: Cell Proliferation Studymentioning
confidence: 99%